Effects of turbulent flow on the corrosion inhibition properties of 2‐mercaptobenzimidazole. Issue 6 (11th January 2012) - Olvera‐Martinez, M. E.; Mendoza‐Flores, J.; Rodriguez‐Gomez, F. J.; Palomar‐Pardave, M. E.; Genesca, J.
Abstract The electrochemical techniques, that is, polarization resistance (Rp) and potentiodynamic polarization curves, were used in order to determine the effect of turbulent flow on the corrosion inhibiting effect of 2‐mercaptobenzimidazole (2‐MBI) on API 5L X52 grade steel samples immersed in a 3% NaCl aqueous solution saturated with CO2 at 60 °C. Turbulent flow conditions were controlled using a rotating cylinder electrode (RCE). An inhibition efficiency of 98% was measured at a concentration of 10 ppm of 2‐MBI at a rotation rate of 5000 rpm. This efficiency value is similar to those efficiency values measured at 25 and 40 ppm 2‐MBI and at the same rotation rate. These observations suggest that as the turbulent flow conditions increase the corrosion inhibiting effect of 2‐MBI is enhanced. 2‐MBI follows a Langmuir adsorption isotherm. The calculated values of adsorption equilibrium constant (Kads) and adsorption free energy ( <![CDATA[$\Delta G_{{\rm ads}}^{{\rm o}} $]]> <inline-graphic xlink:href="ark:/27927/pgg224p99sr" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) suggest that the adsorption process taking place is chemical. The polarization curves indicate that the 2‐MBI does not modify the electrochemical mechanism of the anodic (Fe dissolution) and cathodic (hydrogen evolution) reactions. It is suggested that 2‐MBI decreases the rate at which these reactions occur, blocking the active sites on the steel surface.